The mini-orange magnetic β-spectrometer - J, Sereeter (Scientific transaction of the National University of Mongolia. Physics, 2022)
The brief review available the mini-orange type beta- spectrometers have been made. The various methods for determination of the mini-orange efficiency are discussed. On an example of off-line mini-orange beta-spectrometer of a Department of Nuclear spectroscopy and radiochemistry of Laboratory for Nuclear Problems of JINR, the mini-orange beta-spectrometer as perspective installation for measurement of conversion electrons' spectra from the short-lived neutron- deficient isotopes has been shown.